The un-acknowledged relationship between shared parental leave, breastfeeding and workplace support in UK Universities - Dr. Ernestine Gheyoh Ndzi; Dr. Anjali Raj Westwood (International Journal of Business and Social Science Research, 2021)
Gender equality is integral to a universities’ strategy and agenda. However, there is a gap when looking through the lens of shared parental leave (SPL) or breastfeeding. This research investigates the causal relationship between SPL, breastfeeding, and workplace support. A survey targeting women working in UK Higher Education Institutions was conducted between February and July 2021, and 49 completed responses were recorded. Women reported knowledge of SPL but not all workplaces were offering SPL, it wasn’t easily accessible and often too complex to understand. Breastfeeding policies and workplace resources were minimal. Lack of breastfeeding support on return to work affected women’s decision to take SPL. Recommendations include the creation of more accessible policies (SPL and breastfeeding), providing examples of parents who have utilized SPL, dissemination of information on SPL and breastfeeding when women announce their pregnancy and on return to work, and adequate resources in the workplace to support breastfeeding mothers.